Plan de negocios para la creación de una empresa importadora y comercializadora de repuestos multimarca para maquinaria pesada en Quito con un establecimiento permanente en Florida, Estados Unidos - Lara Toledo, Alejandra Karolina (2017)
Alliance Multiparts is a new company in the market of import and commercialization of parts and pieces for the industry of heavy machinery with a permanent establishment in Miami - United States, whose objective is to provide an effective service to the public and private companies which business turnaround involve the use of heavy machinery in companies eradicated in Pichincha, Cotopaxi, Tungurahua and Imbabura. The reason for the creation of this company when saying that the company will provide an efficient service is to deliver multibrand parts and pieces as soon as possible, with a lower price, with guarantees that prove its originality and quality through strategic alliances negotiated with international suppliers of the company. In every level, both operational and administrative of the company have specialized personnel in their respective areas, which allows a high level of competitiveness in the market that offers the customer a personalized service to each one of its requirements. The permanent establishment in Miami – United States allows his Ecuador´s company Alliance Multiparts search the best offers among its suppliers and negotiate directly with them. In addition, it seeks to implement a logistics chain appropriate to each import done in Ecuador in order to optimize material and intangible resources, in this case the time of the entire import process. Concluding, Alliance is a competitive and attractive project given that the market segment is wide and frequent, adding the positive and profitable results of financial analysis, so over a period of five years is a viable project